Performance of SAF Type Chute and Baffled Chute - Sharma, T.C.; Verma, S.P.; Verma, R.N. (Journal of Soil and Water Conservation, 2022)
Chutes may be called as narrow trough like steep channels in which flow has supercritical velocities. These chutes are commonly used for controlling the steep grades and stabilising gully heads or overfalls. They usually consist of an inlet, steep channel and outlet. Inlet and steep channels are the component parts of chute which accomplish the function of disposing the design runoff by properly gui- ding and conveying the flow. The energy dissipation is accomplished in the stilling basin at the outlet of the structure. The outlet con- sists of various kinds of stilling basins with different modes of energy dissipation. The most common type is SAF ( Saint Anthony Falls) outlet which has a specific configuration of appurtenances and energy is dissipated both by impact and by formation of hydraulic jump. The function of dissipation of energy can also be achieved by obstructing the flow by suitable arrangement of baffles in the steep channel.